Co-Creating Development - Ramaswamy, Venkat (2012)
We are now in a new age of stakeholder engagement. Thanks to the World Wide Web, social media, and advances in mobile and interactive communications and information technologies, networked individuals around the globe are no longer passive and docile recipients of dispensed instructions and development assistance. They are active participants and collaborators in the value creation process, and cocreators of solutions with a wide range of private-public-social enterprises.